2019
DOI: 10.5194/nhess-19-1-2019
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic event-based approach for flood estimation in catchments with mixed rainfall and snowmelt flood regimes

Abstract: Abstract. The estimation of extreme floods is associated with high uncertainty, in part due to the limited length of streamflow records. Traditionally, statistical flood frequency analysis and an event-based model (PQRUT) using a single design storm have been applied in Norway. We here propose a stochastic PQRUT model, as an extension of the standard application of the event-based PQRUT model, by considering different combinations of initial conditions, rainfall and snowmelt, from which a distribution of flood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Also, as we focused only on large annual floods (annual maxima), we did not represent the flood seasonality in our analysis. Yet, some recent works emphasize the need to include such information on the flood type (Brunner et al, 2017) or on flood seasonality (Brunner et al, 2018c) into bivariate analysis of floods or to represent a mixture of both flood type and flood seasonality in flood frequency analysis (Fischer et al, 2016;Fischer, 2018). Thus, the proposed selection methods could potentially be extended to account for different flood types during representative parameter selection, e.g.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as we focused only on large annual floods (annual maxima), we did not represent the flood seasonality in our analysis. Yet, some recent works emphasize the need to include such information on the flood type (Brunner et al, 2017) or on flood seasonality (Brunner et al, 2018c) into bivariate analysis of floods or to represent a mixture of both flood type and flood seasonality in flood frequency analysis (Fischer et al, 2016;Fischer, 2018). Thus, the proposed selection methods could potentially be extended to account for different flood types during representative parameter selection, e.g.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Moreover, as they usually do not simulate antecedent conditions prior to the event and do not account explicitly for storm patterns (duration, spatial and temporal variability), they may yield biased flood frequency distributions (Viglione and Blöschl, 2009;Grimaldi et al, 2012a). Although some modern extensions of this event-based concept account for variable initial conditions prior to the event through sensitivity tests (Filipova et al, 2019), most of the work using event-based simulations assume default initial conditions. Indeed, such event-based simulation is still in use, in particular in the context of probable maximum flood (PMF) estimation based on probable maximum precipitation (PMP) (Beauchamp et al, 2013;Gangrade et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Venegas-Aravena et al (2019) also found that the growth of microcracks and magnetic signals are hosted by these stress conditions within this large area. Recently, large areas of fast stress and strain changes, that surround the impending earthquakes, has been also confirmed by GPS analysis (Bedford et al, 2020).…”
Section: Introductionmentioning
confidence: 57%
“…This indicate that anomalies behavior could correspond to a lithospherical origin. Currently, it has been shown that the origin of these anomalies is associated with the cracking (or micro-cracking) of the semi-fragile-ductile part of the lithosphere (crust) due to changes in stress (Venegas-Aravena et al, 2019). Typically, strain appear when solids undergoes loads or stress accumulation.…”
Section: -Magnetic Anomalies and Fracture Mechanics By Considering The Seismo-electromagnetic Theorymentioning
confidence: 99%
See 1 more Smart Citation